Future Anthropogenic Land Use Change Impacts on Carbonaceous Aerosol and Implications for Climate and Air Quality - Yang Shi; Colette L. Heald; Maria Val Martin (Geophysical Research Letters)
Abstract Future anthropogenic land use change (LUC) may alter atmospheric carbonaceous aerosol (black carbon and organic aerosol) burden by perturbing biogenic and fire emissions. However, there has been little investigation of this effect. We examine the global evolution of future carbonaceous aerosol under the Shared Socioeconomic Pathways projected reforestation and deforestation scenarios using the CESM2 model from present‐day to 2100. Compared to present‐day, the change in future biogenic volatile organic compounds emission follows changes in forest coverage, while fire emissions decrease in both projections, driven by trends in deforestation fires. The associated carbonaceous aerosol burden change produces moderate aerosol direct radiative forcing (−0.021 to +0.034 W/m2) and modest mean reduction in PM2.5 exposure (−0.11 μg/m3 to −0.23 μg/m3) in both scenarios. We find that future anthropogenic LUC may be more important in determining atmospheric carbonaceous aerosol burden than direct anthropogenic emissions, highlighting the importance of further constraining the impact of LUC.